Surgical Outcomes of Chronic Suppurative Otitis Media (Bangladesh Journal of Otorhinolaryngology, 2020)
Objectives: The purpose of this study is to observe the surgical outcomes of chronic suppurative otitis media. 1. To assess the result of surgical procedure to obtain dry and safe ears. 2. To assess the hearing levels after surgery. 3. To observe the complications that occur during the operation and in the immediate postoperative periodMethods: A total 60 patients with CSOM (active squamous variety) who underwent tympanomastoid surgery studied in a period of 1 year from July 2013 to June 2014 at CMH Dhaka.Results: The maximum patients were from15-24 years (35%) age group, male to female ratio was 1.2:1. Highest number of patients (39%) was from middle class family. All the 60 patients presented with discharge from ear and hearing impairment. Maximum (40%) were with attic and postero-superior marginal perforation along with granulation tissue. In 1stpost op month,53 (88.33%) manifested dry ear and in 3rd month after operation 52 (90%) patients manifested dry ear. 7 (11.66%) patients showed discharge from the ear after 1st month which decreased to the 0% after 3rd month. Graft was taken successfully in 56 (93.33%) patients after the first month of operation which reduced to 51 (85%) after third month of operation. Hearing status of the patients before operation proclaimed that 48% patients suffered from moderate hearing loss, 22% and 17% patients suffered from mild and moderately severe loss respectively. 13% patients suffered from severe hearing loss After surgery 86% patients’ condition was improved, 4% patients’ condition deteriorated and 10% patients’ condition remain unchanged . The mean preoperative air-bone gap was 32.10 dB and mean postoperative air-bone gap was 19.10 dB .Bangladesh J Otorhinolaryngol; October 2017; 23(2): 187-194